Implementasi Geocoding Data Alamat Untuk Optimalisasi Strategi Bisnis Dalam Sistem Informasi Geografis - Risma Ekawati (KILAT, 2016)
The strategic location is no longer a guarantee of the company to achieve profitability. It takes more than just a consideration of growing degree of economic and sociological factors of local communities for the agency / company to open the outlet / branch in a new place. The lack of literacy goods or services offered to potential customers around the sales area can result in loss of business while the outlet / branch established strategic place though. Geographic Information System currently has an important role in the business world and help in opening new outlets as well as to prioritize the target market segmentation. Address data assets stakeholders (clients / customers or suppliers or distributors) owned can be optimized to support the business strategy. By using geocoding and data viewer heat maps, the address data can be used to display a blank-spot area where the target market segmentation needs to be done and be considered for the establishment of outlet / branch new.